ALLEGED TOBACCO SMUGGLİNG OF THE HEMAVEND TRIBLE AND ADANA REJI ADMINISTRATION - Dağ, Mustafa (Fırat University, 2021)
In this study, the claims of the Hemavend Tribe about tobacco smuggling in the region during the Adana Regime Administration in the 19th century were evaluated. Since the Ottoman Empire had fertile lands, many ports, important trade routes and a wide trade market, in addition to having wide borders, the phenomenon of smuggling emerged as a problem that occupied the state administrators. This situation not only affected the Empire's trade with foreign states, but also affected local trade. XIX. An example of this situation in the Ottoman Empire in the 19th century occurred in the Adana Reji Administration. There are many reasons for smuggling activities in the Ottoman Empire. However, our aim in this study is that Hemavend Tribe XIX. It is to try to determine the security problems caused by smuggling activities in the region as well as the economic problems throughout the province with the settlement of Adana Province since the middle of the century. In this context, it is especially focused on the tobacco smuggling allegations of the Hemavend Tribe throughout the province. In particular, the process of settlement of Hemavendians in Adana, smuggling activities in the region and the measures taken to prevent such attempts will be discussed. In this context, in this study on Adana Regiment Administration, smuggling and the activities of the Hemavend Tribe It has been prepared by making use of archive documents and provincial yearbooks.

Bu çalışmada, 19. Yüzyılda Adana Reji İdaresi döneminde bölgede Hemavend Aşireti’nin tütün kaçakçılığı ile ilgili iddiaları değerlendirilmiştir. Osmanlı İmparatorluğu, geniş sınırlara sahip olmanın yanı sıra verimli arazilere, pek çok limana, önemli ticaret güzergâhlarına ve geniş bir ticaret pazarına sahip olmasından dolayı kaçakçılık olgusu devlet yöneticilerini meşgul eden bir sorun olarak karşımıza çıkmıştır. Bu durum İmparatorluğun yabancı devletler ile olan ticaretini etkilediği gibi yerel ticareti de etkilemiştir. XIX. Yüzyılda Osmanlı İmparatorluğu’nda yaşanan bu durumun bir örneği Adana Reji İdaresi’nde meydana gelmiştir. Osmanlı İmparatorluğu’nda meydana gelen kaçakçılık faaliyetlerinin pek çok nedeni vardır. Ancak bizim bu çalışmadaki amacımız, Hemavend Aşireti’nin XIX. Yüzyılın ortalarından itibaren Adana vilayetine yerleşmeleriyle birlikte vilayet genelinde ekonomik sıkıntıların yanı sıra bölgede kaçakçılık faaliyetlerin neden olduğu asayiş sorunlarını tespit etmeye çalışmaktır. Bu bağlamda özellikle vilayet genelinde Hemavend Aşireti’nin tütün kaçakçılığı iddiaları üzerinde durmaktır. Bilhassa Hemavendlilerin Adana’ya yerleşme süreçleri, bölgedeki kaçakçılık faaliyetleri ve bu tür girişimlerin önlenmesi amacıyla alınan önlemler ele alınmaya çalışılacaktır. Bu çerçevede Adana Reji İdaresi, kaçakçılık ve Hemavend Aşireti’nin faaliyetlerine dair bu çalışmada arşiv belgelerinden ve vilayet salnamelerinden istifade edilmiştir.
HEMAVEND AŞİRETİ’NİN TÜTÜN KAÇAKÇILIĞI İDDİALARI VE ADANA REJİ İDARESİ